Occupational exposure to trichloroethylene and serum concentrations of IL‐6, IL‐10, and TNF‐alpha. (25th June 2013) - Bassig, Bryan A.; Zhang, Luoping; Tang, Xiaojiang; Vermeulen, Roel; Shen, Min; Smith, Martyn T.; Qiu, Chuangyi; Ge, Yichen; Ji, Zhiying; Reiss, Boris; Hosgood, H. Dean; Liu, Songwang; et al.
<x xml:space="preserve">Abstract</x> To evaluate the immunotoxicity of trichloroethylene (TCE), we conducted a cross‐sectional molecular epidemiology study in China of workers exposed to TCE. We measured serum levels of IL‐6, IL‐10, and TNF‐α, which play a critical role in regulating various components of the immune system, in 71 exposed workers and 78 unexposed control workers. Repeated personal exposure measurements were taken in workers before blood collection using 3 M organic vapor monitoring badges. Compared to unexposed workers, the serum concentration of IL‐10 in workers exposed to TCE was decreased by 70% (P = 0.001) after adjusting for potential confounders. Further, the magnitude of decline in IL‐10 was >60% and statistically significant in workers exposed to <12 ppm as well as in workers with exposures ≥ 12 ppm of TCE, compared to unexposed workers. No significant differences in levels of IL‐6 or TNF‐α were observed among workers exposed to TCE compared to unexposed controls. Given that IL‐10 plays an important role in immunologic processes, including mediating the Th1/Th2 balance, our findings provide additional evidence that TCE is immunotoxic in humans. Environ. Mol. Mutagen. 54:450–454, 2013. © 2013 Wiley Periodicals, Inc.